Heat Stress Induces Oxidative Stress and Predisposes Rats to Gestational Diabetes Mellitus - Mbepera, Saada M.; Mshamu, Shaabani A.; Max, Robert A.; Malago, Joshua J. (Journal of Biology and Life Science, 2023)
Gestational diabetes mellitus (GDM) is a form of hyperglycemia due to carbohydrate intolerance that begins during pregnancy. This may be due to insulin resistance or impairment of insulin secretion during the pregnancy. Several causes of GDM have been identified which include oxidative stress (OS), however the association of heat stress and GDM development during pregnancy is limited. Therefore, this study aimed at examining the association between heat stress and GDM in rats. Pregnant and non-pregnant Wistar rats were maintained at 41 - 42°C for 21 days. On day 1, 8, 15 and 21 of the experiment, animals were humanely sacrificed. Blood samples for glucose, insulin, malondialdehyde (MDA) and glutathione peroxidase (GPx) analyses were collected from the heart. Pancreatic tissues were fixed in neutral buffered formalin, and processed for histopathological studies. The findings demonstrated that, in pregnant rats, heat stress induced a significant increase in glucose linked with a drop in insulin levels than non-pregnant rats (P <0 .05). Also heat treatment was accompanied by an increase in MDA and a drop in GPx levels. Histological examinations of the pancreas revealed damaged β-cells on day 15 and reduction in the number of β-cells by day 21 of the experiment in the pregnant rats. These results suggest that heat stress raises the levels of OS in pregnant rats than non-pregnant rats and increases the chance of GDM as it is associated with β-cell defects in the pancreas.